Service user engagement in health service reconfiguration: a rapid evidence synthesis. (July 2016) - Dalton, Jane; Chambers, Duncan; Harden, Melissa; Street, Andrew; Parker, Gillian; Eastwood, Alison
Objective: To assess what is known about effective patient and public engagement in health service reconfiguration processes and identify implications for further research and health care practice. Methods: Rapid systematic review of published and grey literature to identify methods or approaches to engagement in decisions about health service reconfiguration; and to examine how engagement has worked or not worked in specific examples of system change. Following a search for literature published in English from 2000 to March 2014, eight systematic reviews, seven primary studies and 24 case studies (of which 6 were exemplars) were included. We undertook a narrative synthesis to consider five aspects of engagement with health service reconfiguration. Results: Engagement varied in nature and intensity, and efforts generally involved multiple methods. There was no evidence on the isolated impact of any particular engagement method or collection of methods. In general, engagement was most likely to be successful when started early, when led and supported by clinicians, and when it offered opportunities for genuine interaction. The impact of engagement was variably measured and demonstrated, and frequently defined as process measures rather than the outcomes of proposals for service reconfiguration. Little was reported on the potential negative impact of service user engagement. Conclusions: Patients and the public can be engaged through various methods. Problems often arise because decision-makers paid insufficient attention to issues considered important by patients and the public. Guidance setting out the stages of reconfiguration and opportunities for service user input could be a helpful practical framework for future engagement activity. Future evaluation and explicit reporting of engagement and impact is needed.